The emergence of inflection in bilingual first language acquisition : considerations for theories of grammatical development - Festa, Anna (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2017)
This thesis investigates morphological productivity across two different language types in the early stages of combinatorial speech, based on longitudinal and experimental data from two children who are acquiring two native languages, Italian and English. Generativist-nativist and constructivist models of language development make opposite claims about children’s early productivity in the use of Inflection. The former argue for early mastery of inflections owing to the theoretical assumption that Inflection is an innate functional category; hence, they claim that productivity is achieved as soon as children identify the phonological shapes that inflectional items take in the input language(s). The latter assume item-based acquisition and claim that adult-like use of inflections becomes possible only when children have collected a sufficient number of linguistic structures and begin to run analogies across stored constructions. In addition, several generativist-nativist studies of BFLA children acquiring language pairs that differ in the richness of Inflection have identified cross-linguistic discrepancies in the acquisition of functional items. They have pointed to an advantage in the emergence of inflection-bearing material in the morphologically richer language. Under constructivist accounts, these differences are imputable to the fact that children acquiring richly inflected languages have been credited with adult-like use of inflectional morphology exclusively on the basis of their virtually error-free speech production. BFLA children have often been indicated as excellent testers for cross-linguistic research. In the present study, they are also identified as ideal participants in research about early morphological productivity, because for them the acquisition of each of their languages takes place under reduced exposure, in comparison with their monolingual peers. The aim of this thesis is threefold: firstly, to determine whether BFLA children display adult-like use of inflectional morphology in the early stages of combinatorial speech and whether asymmetries can be identified in the achievement of paradigmatic mastery between their two languages; secondly, to contribute to the on-going debate about competing theoretical accounts of language development; thirdly, to identify operational criteria for the analysis of morphological productivity that are appropriate for naturalistic speech sampling. The factors included in the analysis of productivity are: accuracy in the use of inflections, appearance of bound morphemes with multiple stems, occurrence of function words in varied constructions, knowledge of the obligatory nature of the copula, instances of morphological mixing and production of target-deviant forms. The results from the spontaneously produced speech samples are further tested by examining experimental data, which are used to test the hypothesis that children have knowledge of the obligatory nature of the copula and are able to make contrastive use of verb and noun types in the early stages of combinatorial speech. The data show that the two bilingual first language acquisition children exhibit productive use of the inflectional items targeted in the analysis of the spontaneously produced speech data and that no relevant asymmetries can be identified in the acquisition of Inflection across their two languages. Contrasting results from the experimental data suggest that demands that elicitation tasks pose on very young children are not exclusively of a linguistic nature and may hinder the objective evaluation of their linguistic abilities.
Keywords: Linguistic, Speech & Communication Sciences, Ph.D.; Ph.D. Trinity College Dublin